Teaching the Neglected Art of Persuasive Writing - Suzanne Ehrenberg (Legal Education Review)
The graduate landscape paints an austere outlook for law students with the ultra-competitive legal market fluctuating in its need for graduate lawyers. The experiences of becoming a legal professional that adapts to the complex nature of modern legal roles is being evaluated in the Australian higher education sector. Given that students are enrolled in law degrees in a fast-paced changing world, it is important for legal education institutions to consider how students’ studies, academic achievement and career skills building might be impacted by how they are thinking and feeling about their future. How students feel about and perceive their future affects their level of hope and wellbeing. Hope is defined as an individuals’ positive motivational state and perceived capability to plan and seek pathways to meet their desired goals. This review will consider evidence from the fields of positive psychology, first year experience in higher education, alternative dispute resolution, and teaching and learning pedagogy in order to examine how certain characteristics of the law student experience relates to individual hope. The implications for future research in the field of hope theory, how hope theory can be utilised to inform teaching practices, and the first year law student university experience are discussed while the potential for future research is highlighted in the context of first-year law students’ level of hope and wellbeing.